(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The present study is concerned with the development of analytical models for distribution in miscible fluid flow through porous media. The advection-dispersion equation is solved using Laplace-transform and Duhamel’s theorem with appropriate initial and boundary condition. It is concluded that the concentration distribution of miscible fluids decreases with time.